Adsorption/desorption characteristics of low-concentration semi-volatile organic compounds in vapor phase on activated carbon. (1st March 2022) - Ma, Xiuwei; Yang, Linjun; Hou, Yong; Zhou, Lei
Abstract: The adsorption/desorption behaviors of semi-volatile organic compounds (SVOCs: 1, 2, 3, 4-tetrachlorobenzene (TCB) and phenol) in vapor phase by activated carbon (AC) were investigated by the experiments and density functional theory calculation. Investigations showed that at 100–160 °C, the adsorption capacities of TCB and phenol on AC were in the range of 176.6–342.0 mg/g and 24.0–66.4 mg/g, respectively. Increasing the temperature inhibited the SVOCs adsorption. TCB tended to be adsorbed on AC surface by monolayer, whereas the phenol was multilayer adsorption. The stronger interaction between SVOCs and active sites resulted in a higher desorption temperature (TCB: 255–689 °C; phenol: 200–369 °C). The SVOCs adsorption on AC was fitted well by the pseudo-first-order kinetic model, their lower concentration and larger molecular structure influenced the AC external mass transfer and intraparticle diffusion. TCB and phenol were adsorbed on graphite layer by a parallel manner, their highest adsorption energies were −75.59 kJ/mol and −55.00 kJ/mol, respectively. Oxygen-containing groups altered the charge distribution of the atoms at the edge of the graphite layer, which improved the SVOCs adsorption through enhancement of electrostatic interactions and formation of hydrogen bonds. The carboxyl and lactone groups played a critical role in improving the TCB adsorption capacity, while the carboxyl was important for phenol adsorption. Graphical abstract: Image 1 Highlights: SVOCs have higher adsorption capacity on AC at the temperature of 100–160 °C. Stronger interactions result in a higher desorption temperature of SVOCs. TCB and phenol are adsorbed on graphite layer in a parallel manner. Carboxyl group is the crucial functional group affecting the SVOCs adsorption.